Pengaruh Dukungan Sosial terhadap Kesejahteraan Psikologis Mahasiswa dengan Religiusitas sebagai Moderator - Eva, Nur; Shanti, Pravissi; Hidayah, Nur; Bisri, Moh. (Jurnal Kajian Bimbingan dan Konseling, 2020)
Previous studies have indicated that psychological well-being has a positive contribution to mental health and is a predictor of academic achievement, self-control, life satisfaction, gratitude, optimism, hope, and happiness. Psychological well-being is also influenced by social support and religiosity. This study aimed to examine the effect of social support on students’ psychological well-being, with religiosity as a moderator. This study employed a correlational research design with 354 participants recruited using a simple random sampling technique. Data were collected using a social support scale, a religious scale, and a psychological well-being scale. The data were then analyzed using moderated regression analysis. The results showed that social support contributed significantly to the psychological well-being of students, but religiosity did not increase the contribution of social support to psychological well-being. Based on these results, social support, one of which can be provided through peer counseling, is needed to improve the psychological well-being of students.